Combining ability analysis for seed cotton yield and quality traits in upland cotton (Gossypium hirsutum L.) - K. Bayyapu Reddy; V. Chenga Reddy; M. Lal Ahmed; T.C.M. Naidu and; V. Srinivasarao (Electronic Journal of Plant Breeding, 2017)
Forty five intra-hirsutum hybrids from a 10 × 10 diallel crossing excluding reciprocals along with their parents were evaluated for combining ability for seed cotton yield and its component traits in three environments during kharif, 2013-14. The pooled analysis of variance for combining ability revealed that, the variance due to SCA were higher than GCA variances for all the characters except for days to 50 per cent flowering and 2.5% span length indicating the predominance of non-additive gene action. The estimates of gca effects revealed that the parents NDLH 1938, RAH 1004 and L 770 were found to be best general combiners for yield and its component traits in desired direction. The crosses, NDLH 1938 × L 604, NDLH 1938 × RAH 1004 and NDLH 1938 × L 770, recorded high per se performance (202.18, 197.99 and 195.54 g) and significant positive sca effects (32.12, 22.82 and 19.46) for seed cotton yield plant-1, respectively.